PENGARUH PENDAPATAN ASLI DAERAH DAN BELANJA MODAL TERHADAP PENINGKATAN INDEKS PEMBANGUNAN MANUSIA PADA PEMERINTAH DAERAH DI PROVINSI LAMPUNG PERIODE 2013-2015 - Tia Rizna Pratiwi; Nurdiawansyah Nurdiawansyah (Jurnal Akuntansi dan Keuangan, 2019)
Regional autonomy enacted to give local goverment the authority to increase local revenue and allocative function in local development priorities. this study purpose to determine effect of PAD and capital Expenditure on improving Human Development Index (HDI). This study was conducted in thirteen districts and two cities in the province of Lampung. This study uses budget realization report from two thousand thirteen to two thousand fifteen and HDI two thousand thirteen to two thousand fifteen obtained from auditing firm republic of indonesia province Lampung and website www.bpslampung.go.id. This research has been qualified classical assumption and test feasibility of model, proccesed by regression analysis techiques. Then test hypothesis PAD and capital expenditure showed significant positive effect on the HDI, means increased revenues and capital expenditure, will be increase HDI also. This increased is due ti the allocation of local revenue and capital expenditure has been utilized appropriately so that planned activities can be well.